Auditoría energética del sistema eléctrico del edificio del instituto tecnológico Rumiñahui de la ciudad de Sangolquí durante el año 2016 y su incidencia en el consumo de energía eléctrica. Diseño de un plan de implementación de medidas y acciones de eficiencia energética. - Alcocer Vallejo, Ivan Jony (2017)
The present investigation was carried out at the Instituto Superior Tecnológico Rumiñahui in the city of Sangolquí, where an electrical analysis was carried made based on EEQ (Empresa Eléctrica Quito SA), European Standard UNE-EN 12464-1, Standard for electrical safety in workplaces, respect to the illumination of indoor workplaces, consisted of the identification of current energy uses in each and every area of the building. The recognition of the building, facilities and equipment was made. Also, the current energy situation of the building was known through the collection of historical data of electric consumption through electric bills of the last three years, which showed variations of up to 15% in the consumption of electric energy. These variations were reason enough to carry out an analysis in the electrical system in the building and determined that was necessary to have a plan of energy measures to improve this situation. The plan of measures includes the use of more efficient equipment, time of use, and the implementation of a system of an electric energy usage system to be followed by end users. Activities will allow savings in the monthly bills. The financial resources allocated to electric energy billing affect the economic system of the institution; however it is advisable to make short-term investments for the implementation of more efficient equipment such as luminaires, which will allow a saving of approximately 15% of the current total consumption.